Tooth- and Patient-Related Conditions May Influence Root Canal Treatment Indication - Maria Tereza Pedrosa Albuquerque; Lorena Caetano Abreu; Leticia Martim; Eliseu Aldrighi Münchow; Juliana Yuri Nagata (International Journal of Dentistry)
Aim. To investigate predisposing aspects related to the indication for root canal treatment (RCT) at Dental Schools of Brazil. Methods. Data of 207 patients referred to endodontic treatment at undergraduate Dental Schools of Brazil were collected over a period of 8 months. Patient-related data included age, gender, first dental visit, tooth brushing frequency, number of remaining teeth, and previous endodontic treatment, and tooth-related information regarding number, type, and location in the mouth of teeth that need RCT, waiting time for the endodontic treatment, endodontic diagnosis, pain report, and dental crown condition was collected for each participant. Bivariate analysis (Chi-square test; p<0.05) associated gender and tooth/patient-related conditions. Poisson regression analysis compared multiple endodontic need and exposure variables. Results. Patients were mainly comprised of women (65.2%), aged 18–39 years (69.6%). Previous RCT was significantly more prevalent in women when compared to men p=0.005. First dental visit at later moment (after 20 years of age) demonstrated 400% greater prevalence of multiple RCT demand when compared to patients that attended the dental office at age below seven years p=0.032. Most of the patients presented only one tooth needing RCT (80.2%), mainly premolars (44.9%). Interestingly, women underwent more RCT in maxillary teeth p=0.016 and significantly contributed with their report to the diagnosis process when compared to men p=0.014. Regarding dental crown condition, 45.4% of all teeth registered unsatisfactory restorations, which were more pronounced in female patients p=0.018. Unsatisfactory restorations or dental caries had 75% and 82%, respectively, less prevalence of multiple RCT indication when compared to sound dental crown p=0.001. Conclusions. RCT was undertaken more frequently in young female adults’ premolars presenting unsatisfactory restorations. First dental visit, number of teeth with previous endodontic treatment, tooth group, and dental crown condition were significantly associated with the necessity of multiple endodontic treatments.